Analysis of reading comprehension and disabilities among teenagers - Martín-Ruiz, Isaías; González-Valenzuela, María-José (Anales de Psicología / Annals of Psychology, 2022)
Evolutionary studies that analyse the development of reading comprehension and related difficulties among teenagers are relevant, given importance of this skill for academic performance at this age. The aim of this study is to analyse performance and difficulties in reading comprehension and its components during adolescence. The sample is composed of 203 students aged 12 to 14, in the first, second, and third year of compulsory Secondary Education from a randomly selected school in an average socio-cultural area of Malaga. Students are evaluated for reading comprehension through the selection and organisation of textual ideas, as well as semantic and morpho-syntactic knowledge, after reading a descriptive text. Metacognition is assessed by means of a reading awareness questionnaire. The design is cross-sectional and observational, measuring five variables across three groups of students. A comparison of means and analysis of percentages of difficulties is carried out. The results show significant differences between the groups in the study variables, with the highest scores in the third year. Furthermore, between 15-30% of reading comprehension difficulties are found at these ages. The percentages are higher in the selection and organisation of ideas across all three school years examined, and the percentages are higher in the third year for all the variables. These results imply the need to control the teaching-learning processes of reading comprehension from an early age, in order to avoid difficulties in the first few years of secondary education.